Effects of carbohydrate and protein co-ingestion during short-term moderate-intensity exercise on cognitive function - Sun, F. H.; Cooper, S. B.; Gui, Z. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: This study aimed to investigate the effects of isocaloric carbohydrate-electrolyte solution (CES) and carbohydrates-electrolyte-protein solution (CEPS) consumed during moderate-intensity exercise on cognitive function. METHODS: Twenty-three healthy participants (age: 21.7±1.5 years, Body Mass Index: 21.8±2.0 kg/m2, and peak oxygen consumption (VO2peak): 42.4±6.9 mL/kg/min) were recruited in the study. Participants completed two main experiment trials using a cross-over study design. In each trial, they completed 30 minutes of 70% VO2peak cycling, and one of two solutions (CES or CEPS) was consumed. A battery of cognitive function tests (imPACT Package) was administrated at rest and immediately post-exercise. RESULTS: Blood glucose concentrations decreased in both trials. Heart rate and blood lactate concentrations increased in both trials. However, no significant main effects of the exercise on all cognitive function variables (verbal and visual memory, visual-motor speed, reaction time, impulse control, and cognitive efficiency index) were observed (all P>0.05). Also, there was no difference in any of the cognitive function variables between the CES and CEPS trials (all P>0.05). CONCLUSIONS: There was no difference in the cognitive performance when CES or CES-PRO solutions was consumed during 30 minutes moderate-intensity cycling.